Self-Assembly of the Bio-Surfactant Aescin in Solution: A Small-Angle X-ray Scattering and Fluorescence Study - Carina Dargel; Ramsia Geisler; Yvonne Hannappel; Isabell Kemker; Norbert Sewald; Thomas Hellweg (Colloids and Interfaces, 2019)
This work investigates the temperature-dependent micelle formation as well as the micellar structure of the saponin aescin. The critical micelle concentration ( <semantics> c m c </semantics> ) of aescin is determined from the concentration-dependent autofluorescence (AF) of aescin. Values between <semantics> c m c aescin , AF </semantics> (10 <semantics> ∘ </semantics> C) = 0.38 ± 0.09 mM and <semantics> c m c aescin , AF </semantics> (50 <semantics> ∘ </semantics> C) = 0.32 ± 0.13 mM were obtained. The significance of this method is verified by tensiometry measurements. The value determined from this method is within the experimental error identical with values obtained from autofluorescence ( <semantics> c m c aescin , T ( WP ) </semantics> (23 <semantics> ∘ </semantics> C) = 0.33 ± 0.02 mM). The structure of the aescin micelles was investigated by small-angle X-ray scattering (SAXS) at 10 and 40 <semantics> ∘ </semantics> C. At low temperature, the aescin micelles are rod-like, whereas at high temperature the structure is ellipsoidal. The radii of gyration were determined to ≈31 Å (rods) and ≈21 Å (ellipsoid). The rod-like shape of the aescin micelles at low temperature was confirmed by transmission electron microscopy (TEM). All investigations were performed at a constant pH of 7.4, because the acidic aescin has the ability to lower the pH value in aqueous solution.